2005
DOI: 10.1007/s00192-005-0007-4
|View full text |Cite
|
Sign up to set email alerts
|

Posterior intravaginal slingplasty for vaginal prolapse

Abstract: The posterior IVS delivered satisfactory results for vault and posterior compartment prolapse, with a 75% improvement in vault prolapse. It was not possible, however, to separate the effect of posterior IVS and posterior colporrhaphy on the prevention of recurrent prolapse nor on the improvement of difficulty in defecation. Due to the utilization of the now-abandoned vaginal anterior colposuspension procedure for the treatment of anterior compartment prolapse, no conclusions regarding the impact of the posteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
3
5

Year Published

2007
2007
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 8 publications
2
17
3
5
Order By: Relevance
“…The incidence of mesh erosion ranged from 0% to 10%. The earlier studies had fewer numbers of patients than our current study (42-44) [10][11][12]. A recent study by Neuman and Lavy reported on the follow-up of 140 patients and showed a 10% incidence of mesh erosion [12].…”
Section: Discussioncontrasting
confidence: 40%
“…The incidence of mesh erosion ranged from 0% to 10%. The earlier studies had fewer numbers of patients than our current study (42-44) [10][11][12]. A recent study by Neuman and Lavy reported on the follow-up of 140 patients and showed a 10% incidence of mesh erosion [12].…”
Section: Discussioncontrasting
confidence: 40%
“…In none of the studies were complications separately described for the subgroup of women in which the uterus was preserved. Therefore, for describing complications, we used data for women who underwent a posterior intravaginal slingplasty with and without preservation of the uterus [37][38][39][40][41][42][43][44][45][46][47].…”
Section: Study Selectionmentioning
confidence: 99%
“…Therefore, after cervical amputation, a risk of stenosis is present, which could influence the occurrence of alarming symptoms (vaginal blood loss) in the development of adenocarcinoma of the uterus. After a posterior intravaginal slingplasty (with and without preservation of the uterus) mesh erosion problems were reported in 0% to 21% of women [37][38][39][40][41][42][43][44][45][46][47]. Baessler et al described erosion problems in 13 women who were referred to their clinic after implantation of a multifilament mesh at other clinics [56].…”
Section: Surgical Proceduresmentioning
confidence: 99%
See 2 more Smart Citations